The use of Learning Video Media to Improve Science Skills in Fifth Grade Elementary School Students - Yulianingrum, Dewi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study is to improve students' understanding of science learning in grade V SD. This research is a classroom action research conducted in 3 cycles. Each cycle consists of stages of planning, implementing, observing and reflecting. The subjects of this study were 17 students of grade V SD Negeri Nglondong. Data collection techniques using observation and tests. Data analysis includes data reduction, data presentation and drawing conclusions. Research shows that the use of video media can improve students' understanding of science class V SD in the 2020/2021 academic year as evidenced by the percentage of completeness of learning outcomes and the class average. In the first cycle of 52.9% with a class average of 71.18 to 100% with an average of 86.47 in the second cycle and in the third cycle it was 100% complete with a class average of 95.29.